Enhancing understanding of endometrial function in patients with PCOS: clinical and immunological insights - Yaxin Guo; Jingfei Yang; Hong Chen; Yueping Zhou; Yan Yang; Biao Wang; Luyang Zha; Dijia Bai; Wenxuan Li; Xiaojuan Tang; Zishui Fang; Fei Li; et al. (Journal of Ovarian Research)
Abstract Objective To evaluate the pregnancy and perinatal outcomes of different phenotypes of polycystic ovary syndrome (PCOS) patients during the frozen embryo transfer (FET) cycles. Additionally, to analyze the T cell balance in the endometrium of PCOS patients and explore its relationship with various PCOS phenotypes. Design Retrospective cohort study. Setting A single academically affiliated reproductive medicine center. Patients 21,074 FET cycles were included and divided into two groups based on the diagnosis of PCOS. Patients with PCOS were further categorized into four phenotypic groups: PCOM + HA + OA, PCOM + HA, PCOM + OA, and HA + OA. Endometrial biopsies from 21 PCOS patients and 26 controls were obtained to analyze T cell subsets. Methods Pregnancy and perinatal outcomes, as well as T cell subset abundance were compared between women with and without PCOS. Multiple logistic regression models were employed to adjust for confounding factors impacting pregnancy-related outcomes. Flow cytometry was utilized to analyze the abundance of T cell subsets. Main outcome measures Pregnancy and perinatal outcomes were assessed. T cell subsets including CD4+CD8−T cells, CD4−CD8+T cells, Th1, Th2, Th17 and Treg cells in the endometrium were determined by flow cytometry. Results There was a significantly increased incidence of miscarriage, hypertensive disorders of pregnancy (HDP), preterm birth (PTB), and even fetal malformations across different phenotypes of PCOS women, especially those with the hyperandrogenic phenotype. Th1 cells decreased while Th2 cells increased significantly in the PCOS endometrium. Conclusions The unfavorable pregnancy and perinatal outcomes in FET cycles and T cell imbalance both suggest the endometrial dysfunction of PCOS patients, especially those with the hyperandrogenic phenotype.